Quantification of Urinary Protein Biomarkers of Autosomal Dominant Polycystic Kidney Disease by Parallel Reaction Monitoring. Issue 5 (2nd May 2018) - Rauniyar, Navin; Yu, Xiaoqing; Cantley, Jennifer; Voss, Edward Z.; Belcher, Justin; Colangelo, Christopher M.; Stone, Kathryn L.; Dahl, Neera; Parikh, Chirag; Lam, TuKiet T.; Cantley, Lloyd G.
Abstract : Purpose: Autosomal dominant polycystic kidney disease (ADPKD) is a life‐long disease in which the genes responsible are known, but the pathogenesis of cyst formation and cyst growth are not understood. Cyst growth ultimately leads to end‐stage renal failure in most patients. Analysis of the urinary proteome offers the potential to identify proteins that indicate the presence of cysts (and thus provides diagnosis) as well as the rates of cyst growth (providing prognostic information). Experimental design: A scheduled parallel reaction monitoring (sPRM) assay is performed on urine samples from 14 patients and 18 normal controls. For relative quantification, stable isotope‐labeled synthetic peptides are spiked in the urinary protein digests prior to data collection. The data are subsequently normalized to creatinine and protein concentration in the respective urine samples to control for variations in water intake between individuals. Results: Out of the 143 urinary proteins targeted for sPRM assay, 69 proteins are observed to be significantly dysregulated in ADPKD. The dysregulated proteins are used to cluster ADPKD patients into those who are more or less similar to normal controls. Conclusions and clinical relevance: This study shows that sPRM is a promising approach to rapidly screen large numbers of proteins in urine in order to provide earlier diagnosis and potentially better understand the pathogenesis of ADPKD development and progression.